2017
DOI: 10.1080/10942912.2017.1343350
|View full text |Cite
|
Sign up to set email alerts
|

Boiling point and specific heat of meat extract

Abstract: Meat extract is a by-product obtained from the cooking broth of meat processing, which is used as a flavoring agent in cooking and in pharmaceutical products. Information on the processing technology of meat extract and its corresponding thermodynamic properties have been seldom reported, making difficult the design of heat transfer processes with accuracy. Thus, the present work aimed to evaluate the boiling-point elevation (BPE) and specific heat (c p ) of meat extract in the range of concentrations and temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Regarding the temperature, Figure 2(d)-(f) also showed that specific heat slightly increases with increasing temperature. This same trend was noticed for Cabernet Sauvignon grape juice (Castilhos et al, 2017), Merlot grape juice (Castilhos et al, 2018), juices and syrups from a noncentrifugal sugar cane production process (Alarcón et al, 2020), meat extract (Polachini, Betiol, Bastos, Telis, & Telis-Romero, 2017), pequi pulp (Souza, Queiroz, Figueirêdo, Santos, & Lemos, 2016) and papaya puree (Tansakul, Kantrong, Saengrayup, & Sura, 2012). So, it could be assumed that diluted solutions demand more energy to increase the temperature than concentrated solutions with the same mass.…”
Section: Specific Heat (C P )supporting
confidence: 61%
“…Regarding the temperature, Figure 2(d)-(f) also showed that specific heat slightly increases with increasing temperature. This same trend was noticed for Cabernet Sauvignon grape juice (Castilhos et al, 2017), Merlot grape juice (Castilhos et al, 2018), juices and syrups from a noncentrifugal sugar cane production process (Alarcón et al, 2020), meat extract (Polachini, Betiol, Bastos, Telis, & Telis-Romero, 2017), pequi pulp (Souza, Queiroz, Figueirêdo, Santos, & Lemos, 2016) and papaya puree (Tansakul, Kantrong, Saengrayup, & Sura, 2012). So, it could be assumed that diluted solutions demand more energy to increase the temperature than concentrated solutions with the same mass.…”
Section: Specific Heat (C P )supporting
confidence: 61%
“…They consist of a specific apparatus that enables energy balancing when heat is provided to the sample inside the bottle [23]. In order to provide more accurate and rapid data, the use of a differential scanning calorimeter (DSC) has become increasingly popular [24], currently representing the most used method for estimation of specific values and their temperature dependence in different applications [11,25,26].…”
Section: Specific Heat (C P )mentioning
confidence: 99%
“…A study in [15] showed that an improved psychrometer was developed to solve practical problems in measuring the relative humidity of drying environments, which are challenging for meat production. Besides, research on the boiling point and specific heat of meat extract was done [16]. Meanwhile, the effect of thermal processing on nutrition, anti-nutritional and antioxidant properties of Tetracarpidium conophorum (African walnut) was studied in [17].…”
Section: Introductionmentioning
confidence: 99%